Avaliação da vulnerabilidade à perda de solo da bacia hidrográfica do rio Icamaquã - RS - Scotto, Lucas Noremberg (2012)
The management and the territorial regulations for the sustainable use of natural resources demand knowledge concerning the environmental restrictions and potentialities. Thus, the methodology that was developed for the Ecological-Economic Zoning (ZEE) allows the definition of areas with greater or smaller susceptibility to occupation, according to socio-economical and physical environment criteria. Being this work directed to the ecologic zoning it had as objective to identify in Icamaquã River hydrographic basin located on Pampa biome in the state of Rio Grande do Sul - Brazil. This methodology uses Landsat5/TM orbital images and information the area regarding geomorphology, geology, pedology, climate, land use and cover, which permitted to evaluate the process of landscape alteration in a Geographic Information System. The results organized into a database allowed the identification of the vulnerability classes to soil loss that are prevailing within the study area, as well as the search for information, which is useful for the planning and the management activities of hydrographic basins..